Systematic review of the economic burden of dengue infection to the healthcare in South East Asia (SEA) - Mohd ‘Ammar Ihsan Ahmad Zamzuri; Shahrul Azhar Md Hanif; Ahmad Farid Nazmi Abdul Halim; Muhammad Ridzwan Rafi’i; Siti Najiha Md Asari; Rozita Hod; Rahmat Dapari; Hasanain Faizal Ghazi; Mohd Rohaizat Hassan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Dengue remains a public health threat that consumes a significant number of resources for its prevention and control. This systematic review aimed to solidify recent costing evidence in dengue management among South East Asian (SEA) countries. All studies conducted between 2010 and 2020 were retrieved using four international databases i.e. PubMed, Scopus, Web of Science, and Emerald Insight. The review was reported according to PRISMA guidelines. Quality assessments were done independently by two reviewers using a checklist adapted for the cost of illness studies. We identified 13 original articles representing several SEA countries. Among the common reported costing measure include total cost/ health expenditure; direct medical cost; direct non-medical cost; and indirect cost. The estimated total cost for dengue management varied between countries largely due to the difference in the total incidence of dengue cases. The estimated cost spent on dengue per capita GDP ranges from less than 0.001% to 0.1%, depending on the recorded number of dengue cases of the year. The majority of the articles focused on the economic burden from the perspective of treatment such as hospitalization and ambulatory care. In a nutshell, the economic burden of managing dengue infection is costly and the evidence suggests a steady increase in health expenditure with the growing number of dengue cases.